Serum carboxymethyl-lysine and soluble receptor for advanced glycation end products in hyperthyroid and hypothyroid patients - YAVUZ, DİLEK (My University, 2022)
Purpose. The formation and accumulation of advanced glycation end products (AGEs) are enhanced with increased oxidative stress and inflammatory conditions. A hyperthyroid and hypothyroid state is associated with oxidative stress. This study aimed to evaluate skin AGE deposition, serum carboxymethyl-lysine (CML), and serum soluble receptor for AGEs (sRAGE) levels in hypothyroid and hyperthyroid patients. Methods. A total of 203 subjects were included in this cross-sectional study. After excluding diabetes mellitus, 103 newly diagnosed hypothyroid patients, 50 newly diagnosed hyperthyroid patients, and 50 control (euthyroid) subjects were enrolled. All tests were done before beginning the appropriate treatment. Accumulated AGEs in the skin collagen were measured by skin autofluorescence (SAF) using an AGE Reader. Results. SAF measurements were 1.82 ± 0.04, 1.80 ± 0.40, and 1.63 ± 0.30 arbitrary units for the hypothyroid, hyperthyroid, and euthyroid groups, respectively (p = 0.04). Serum CML levels were 8.2 ± 2.8, 10.2 ± 2.0, and 8.0 ± 3.3 ng/mL for the hypothyroid, hyperthyroid, and euthyroid groups, respectively (p = 0.01). sRAGE levels were similar between the groups. Serum thyroid-stimulating hormone and SAF measurements were positively correlated (r = 0.25, p = 0.02) in the hypothyroid group and negatively correlated in the hyperthyroid group (r =-0.36, p = 0.04). There was no correlation between CML and sRAGE levels. Conclusion. SAF measurements are increased in both hypo-and hyperthyroid normoglycemic patients. Serum CML levels are increased in hyperthyroid patients. Hypo and hyperthyroid states might be associated with acceleration of AGE accumulation and may have a long term effect on metabolic memory.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endokrin ve Otonom Sistemler; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; Endocrine and Autonomic Systems; advanced glycation end products; hyperthyroidism; hypothyroidism; skin autofluorescence; soluble receptor for advanced glycation end products